2015
DOI: 10.1111/cup.12539
|View full text |Cite
|
Sign up to set email alerts
|

Angiolymphoid hyperplasia with eosinophilia developing within a port wine stain

Abstract: A 19-year-old male with a port wine stain on the base of his neck presented with a 5-month history of gradual thickening of the involved skin which interfered with clothing and caused repeated bleeding. The lesion was excised and histopathologic examination revealed angiolymphoid hyperplasia with eosinophilia (ALHE) arising from the pre-existing port wine stain - a rare finding with only one previously reported case. Additionally the lesion was associated with elevated serum renin levels which virtually normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Association with arteriovenous shunts in 43% of cases of ALHE strengthens the conclusion that the entity may represent a vascular neoplastic proliferation [ 7 ]. ALHE has also been reported to develop within a port wine stain in a patient, and the authors highlighted the role of increased serum renin levels in the pathogenesis of this case in which the histopathology specimen revealed expression of angiotensin converting enzyme and angiotensin II receptors [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Association with arteriovenous shunts in 43% of cases of ALHE strengthens the conclusion that the entity may represent a vascular neoplastic proliferation [ 7 ]. ALHE has also been reported to develop within a port wine stain in a patient, and the authors highlighted the role of increased serum renin levels in the pathogenesis of this case in which the histopathology specimen revealed expression of angiotensin converting enzyme and angiotensin II receptors [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 116 ALHE patients, 10 cases (9%) were found to be associated with antecedent trauma (frostbite, surgery, laceration, frictional trauma, and other unspecified) with a time course between injury and the onset of lesions ranging from 7 months to 20 years (median, 30 months) [ 8 ]. This phenomenon has also been described in pyogenic granulomas, another vascular proliferative disorder, which developed after thermal burn, lightning, or mine injury [ 9 ].…”
Section: Discussionmentioning
confidence: 99%